Restructuring Strategy of State Owned Municipal Solid Waste Company at PD. Kebersihan Bandung Indonesia 2012 - Budiman, Luthfi; Anggono, Achmad Herlanto (The Indonesian Journal of Business Administration, 2012)
PD. Kebersihan is Bandung Government owned company that responsible for managing municipal solid waste in Bandung. The purposes of PD.Kebersihan as a state owned company is expected to do municipal solid waste management service and can support the local government revenue. The identification analysis has found that the problems in PD.Kebersihan are from financial, operational, and organizational activity. This identification has also shown that the company is not surviving recently, but the material support and non-material support such as guarantee and financial subsidized that given by the local government has save this company. The companyÃ¢â‚¬â„¢s problems can be solved by using the turnaround strategy, which mean that the restructuring would be imposed through the operational, organizational, and financial changes by using several methods such as management review, activity based costing, and TOWS matrix. The restructuring process will take one-year program. The process are consists of changes in retribution tariff and billing system, cutting ineffective employees, rescheduling in international loan debt, adding new technology, adding new sources of income, changing the subsidized income to become the public service income, creating the business process and business model mapping and creating the value proposition to enhance employees performance, motivation, and discipline. Cost of restructuring will take Rp. 43,355,200,000, - and will be projected in three scenarios such as worse scenario, most likely scenario, and optimistic scenario. The returned value is calculated based on several methods such as NPV, IRR, and MIRR. This methods are planning to have a value return in projection at sequences (Rp. 20,866,154,012 - Rp. 112,689,078,895), (24% - 91%) and (23% - 71%). The payback period will be planned at 1.6-2.7 years. The restructuring results will also be planned to raise revenue for 17% CAGR, lowering operational cost for 2% CAGR and raising employeeÃ¢â‚¬â„¢s prosperity for 32% in 5 years projection. The value of risk in restructuring program is calculated by comparing the sum of money that government should to pay in case of subsidized or public service payment in 5 years (2012-2016). The risk has been analyzed in case the program is not running well. The cost of risk for this program is 9.89% of the 5 years government subsidized projection. If the restructuring program applied and become success then the government of Bandung will gain benefit for reducing the public service payment for 44.3% of the 5 years government subsidized projection. Company valuation is based on the 5 years projection (2012-2016). The future value in 2016 is predicted to be Rp.438,497,803,914, and the present value in 2012 is predicted to be Rp.244,252,233,875. Company valuation is aimed for gaining more capital from public if the government decided to make this company go public. Ã‚Â Keyword: Municipal Solid Waste Management, Public Service, financial, operational, organizational, government, cleanliness, restructuring, retribution, subsidized, scenario, risk.